2022
DOI: 10.1186/s12935-022-02513-1
|View full text |Cite|
|
Sign up to set email alerts
|

miR-223-3p carried by cancer-associated fibroblast microvesicles targets SORBS1 to modulate the progression of gastric cancer

Abstract: Background Cancer-associated fibroblasts (CAFs) aggravate gastric cancer (GC) development. Methods Combined with bioinformatics analysis and literature review, miR-223-3p had high expression in microvesicles (MVs) derived from GC CAFs, and it could modulate SORBS1. miR-223-3p and SORBS1 mRNA levels were assessed by qRT-PCR. The levels of CAFs markers, MVs markers, epithelial-mesenchymal transition (EMT)-associated proteins, and SORBS1 protein were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Thus these ve circRNAs may be involved in the regulation of adhesion phenotype, among which the host gene SORBS1 of circ-SORBS1 is also a differentially expressed gene, which has aroused our attention. Jin et al [19] found that SORBS1 can be targeted by miRNA to regulate the progression of gastric cancer, suggesting that circ-SORBS1 may regulate the expression of its host genes by targeting miRNA, which was con rmed in the analysis of this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus these ve circRNAs may be involved in the regulation of adhesion phenotype, among which the host gene SORBS1 of circ-SORBS1 is also a differentially expressed gene, which has aroused our attention. Jin et al [19] found that SORBS1 can be targeted by miRNA to regulate the progression of gastric cancer, suggesting that circ-SORBS1 may regulate the expression of its host genes by targeting miRNA, which was con rmed in the analysis of this study.…”
Section: Discussionsupporting
confidence: 77%
“…3a), among which sorbin and SH3 domain-containing protein 1 (SORBS1) attracted our attention due to it was involved in the adherens junction pathway. It has been reported that SORBS1 can be targeted by miRNA to regulate the progression of gastric cancer [19]. These results suggest that circ-SORBS1 may be an important candidate circRNAs involved in the biogenesis of E. coli diarrhea.…”
Section: Differentially Expression Circrnas In Piglet Small Intestina...mentioning
confidence: 75%
“…In the research study of CAFs, Wand et al (12) demonstrated that MMP14, LOXL2, and POSTN are characterized by high expression of genes associated with gastric tumor invasion. The previous research studies found that SORBS1, IL-6, MUC1, FGF9, KLF5, SPARC, TEM1, NRP2, CXCL12, RHBDF2, SAA1, and VCAM are significant expressions in CAF and have an association with GC (7,8,13,(16)(17)(18)(19)(20)(21)(22)(23)(24). According to our search in research papers from PubMed, we chose the 18 genes (MMP11, HAPLN1, IL-33, IL-6, SORBS1, MUC1, FGF9, KLF5, SPARC, TEM1, VCAM1, POSTN, MMP14, LOXL2, NRP2, CXCL12, RHBDF2, and SAA1) that related to CAFs in GC.…”
Section: Defining the Caf-related Regulatorsmentioning
confidence: 99%
“…Other CAFrelated genes, such as mucin 1 (MUC1), Krüppel-like Zinc-Finger Transcription Factor 5 (KLF5), tumor endothelial marker 1 (TEM1), vascular adhesion molecule 1 (VCAM1), periostin (POSTN), lysyl oxidase like 2 (LOXL2), neuropilin-2 (NRP2), rhomboid 5 homolog 2 (RHBDF2), and serum amyloid A1 (SAA1), are characterized by high expression of genes associated with a poor prognosis in patients with GC (12,(16)(17)(18)(19)(20)(21)(22). In contrast, CAF-related genes such as Sorbin and SH3 domain-containing protein 1 (SORBS1), and secreted protein acidic and rich in cysteine (SPARC) have a significantly low expression in CAF and are closely related to poor prognosis in GC (23,24). Carcinogenesis and development are characteristic of the interaction between multiple genes and signal pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In this article [ 1 ], the data and p value of the Western Blot histogram were found. Due to the software operation error, a calculation error occurred.…”
Section: Correction To: Cancer Cell International (2022) 22:96 ...mentioning
confidence: 99%